Sustainable growth and economic development a case study of Malaysia - Mahadevan, Renuka (Edward Elgar, 2007)
Provides an insight into some of the efforts and actions taken by the developing economy of Malaysia towards its 'Vision 2020' of becoming a developed country. This book explores whether the vision can become reality and not just remain a dream.